Dynamic factor models - Hillebrand, Eric.; Koopman, S. J. (Siem Jan) (Bingley, U.K. : Emerald, 2016)
Dynamic factor models (DFM) constitute an active and growing area of research, both in econometrics, in macroeconomics, and in finance. Many applications lie at the center of policy questions raised by the recent financial crises, such as the connections between yields on government debt, credit risk, inflation, and economic growth. This volume collects a key selection of up-to-date contributions that cover a wide range of issues in the context of dynamic factor modeling, such as specification, estimation, and application of DFMs. Examples include further developments in DFM for mixed-frequency data settings, extensions to time-varying parameters and structural breaks, for multi-level factors associated with subsets of variables, in factor augmented error correction models, and in many other related aspects. A number of contributions propose new estimation procedures for DFM, such as spectral expectation-maximization algorithms and Bayesian approaches. Numerous applications are discussed, including the dating of business cycles, implied volatility surfaces, professional forecaster survey data, and many more.
An overview of the factor-augmented error-correction model / Anindya Banerjee, Massimiliano Marcellino, Igor Masten -- Estimation of VAR systems from mixed-frequency data : the stock and the flow case / Lukas Koelbl ... [et al.] -- Modeling yields at the zero lower bound : are shadow rates the solution? / Jens H.E. Christensen, Glenn D. Rudebusch -- Dynamic factor models for the volatility surface / Michel van der Wel, Sait R. Ozturk, Dick van Dijk -- Analyzing international business and nancial cycles using multi-level factor models : a comparison of alternative approaches / Jo<U+0308>rg Breitung, Sandra Eickmeier -- Fast ML estimation of dynamic bifactor models : an application to European inflation / Gabriele Fiorentini, Alessandro Galesi, Enrique Sentana -- Country shocks, monetary policy expectations and ECB decisions. A dynamic non-linear approach / Maximo Camacho, Danilo Leiva-Leon, Gabriel Perez-Quiros -- Modelling financial markets comovements during crises : a dynamic multi-factor approach / Martin Belvisi, Riccardo Pianeti, Giovanni Urga -- Specification and estimation of Bayesian dynamic factor models : a Monte Carlo analysis with an application to global house price comovement / Laura E. Jackson ... [et al.] -- Small versus big-data factor extraction in dynamic factor models : an empirical assessment / Pilar Poncela, Esther Ruizy -- Regularized estimation of structural instability in factor models : the US macroeconomy and the great moderation / Laurent Callot, Johannes Tang Kristensen -- Dating business cycle turning points for the French economy : an MS-DFM approach / Catherine Doz, Anna Petronevich -- Common faith or parting ways? A time varying parameters factor analysis of euro-area inflation / Davide Delle Monache, Ivan Petrella, Fabrizio Venditti -- Nowcasting business cycles : a Bayesian approach to dynamic heterogeneous factor models / Antonello D'Agostino ... [et al.] -- On the selection of common factors for macroeconomic forecasting / Ale
Print version record
Keywords: Business & Economics -- Economics -- Macroeconomics; Econometrics; Macroeconomics; Macroeconomics -- Econometric models